HUBUNGAN PERSONAL HYGIENE DAN PERILAKU MENJAGA KEBERSIHAN LINGKUNGAN SEKOLAH DENGAN KEJADIAN ASCARIASIS DI SDN 04/IV ARAB MELAYU KEC. PELAYANGAN KOTA JAMBI - Slamet Afriyadi; Miko Eka Putri (Universitas Baiturrahim, 2016)
Background : Worm infection is one of the most common diseases spread and infect many children around the world, the prevalence of intestinal worms in Indonesia is still high, between 45-65%, in certain areas the poor environmental conditions could reach 80%. Factors personal hygiene and environmental sanitation is an important factor in this disease. Factors personal hygiene and environmental sanitation is an important factor in this disease.Method : This research was conducted at SDN 04/IV Jambi that have been conducted on 27-30 July 2015 aims to determine the relationship of personal hygiene and behavior of keeping the environment clean school with ascariasis incidence. Quantitative research methods descriptive cross-sectional design. Sample of 37 people were taken by proportional random sampling. Collecting data using laboratory test, and questionnaire. Statistical test used chi-square test using a significance level of 5% (0.05).Result : The survey results revealed that most respondents (54.1%) have good personal hygiene, most respondents (51.4%) had behavioral maintain the cleanliness of the school environment is not good, and the majority of respondents (54.1%) positive with ascariasis. Results reveal that there is a significant association between the occurrence of ascariasis personal hygiene with a p-value of 0.003 (P <0.05) and there was a significant correlation between the behavior of maintaining the cleanliness of the school environment with the incidence of ascariasis with a p-value 0.022 (P <0.05).Expected to students to implement PHBS in everyday life and to the school is expected to facilitate the existing facilities and infrastructure in schools and to community health centers are expected to be able to conduct counseling on ascariasis and periodic checks on elementary school children.Keywords: Personal hygiene, behavioral maintain the cleanliness of the school environment, the incidence of ascariasis